Ideas irracionales y su influencia en la ansiedad de una estudiante de 15 años - Baños Escobar, Wilson Israel (2020)
What is the reality? Or the right question would be: What is it that makes reality or life meaningful? The meaning of everything around us is the process or attributions of our own thoughts about what surrounds us as good and evil, since for some things that happen will be a good event and for others they will be negative events . Moral beliefs and values, in the perspective of a country, would be considered as customs of its culture and qualified as an appropriate style. The same in another country with a different culture would be inappropriate. Therefore, the considerations of our environment and our social relations, the desires and goals that each of us sets out, go in the direction of the sense of the beliefs that are given to them. However, when the thoughts constructed to obtain or achieve our desired desires are demanding, and without a logical basis, they lead the individual to a state of intolerance and frustration creating in itself a threatening reality.